ENSO and Southeast Asian biomass burning modulate subtropical trans-Pacific ozone transport. Issue 6 (13th June 2020) - Xue, Lian; Ding, Aijun; Cooper, Owen; Huang, Xin; Wang, Wuke; Zhou, Derong; Wu, Zhaohua; McClure-Begley, Audra; Petropavlovskikh, Irina; Andreae, Meinrat O; Fu, Congbin
Abstract: Trans-Pacific transport of enhanced ozone plumes has been mainly attributed to fossil fuel combustion in Asia in spring, but less attention has been paid to vegetation fires in Asia. Here we show that the El Niño-Southern Oscillation (ENSO)-modulated fires in Southeast Asia, rather than Asian fossil fuel plumes, dominate the interannual variability of springtime trans-Pacific transport of ozone across the entire North Pacific Ocean. During El Niño springs, the intensified fires from both the Indochinese Peninsula and Indonesia, together with large-scale circulation anomalies, result in enhanced ozone plumes that stretch over 15 000 km in both the lower-middle and upper troposphere. This enhancement is also observed in the in situ measurements of ozone concentration, with an almost 10% increase at Mauna Loa Observatory, Hawaii, a unique site to monitor the long-distance transport over the North Pacific. This study reports an unexpectedly strong influence of vegetation fires, linked with climate variability, on global tropospheric chemistry and proves once more how complex the interactions in the climate system are.